Supramolecular nanomedicine derived from cucurbit[7]uril-conjugated nano-graphene oxide for multi-modality cancer therapy. (20th April 2021) - Ding, Yuan-Fu; Kwong, Cheryl H. T.; Li, Shengke; Pan, Ya-Ting; Wei, Jianwen; Wang, Lian-Hui; Mok, Greta S. P.; Wang, Ruibing
Abstract : Cucurbit[7]uril functionalized nano-graphene oxide was developed for the first time, onto which drugs and adamantane-tagged hyaluronic acid were loaded for targeted combined chemo-phototherapy of cancer. Abstract : Nano-graphene oxide (NGO) has attracted increasing attention as an advanced drug delivery system. However, the current surface functionalization and drug-loading of NGO either rely on π–π stacking that is limited to aromatic molecules, or covalent conjugation that requires tedious synthesis. Herein, we developed the first cucurbit[7]uril (CB[7])-conjugated NGO (NGO-CB[7]) that allows non-covalent, modular surface functionalization and drug loading via not only traditional π–π stacking interactions between the NGO surface and functional molecules, but also strong host–guest interactions between CB[7] and guest payloads or adamantane (ADA)-tagged functional molecules, for more versatile biomedical applications. To this end, chlorin e6 (Ce6, a photosensitizer), banoxantrone dihydrochloride (AQ4N, a hypoxia-responsive prodrug) and oxaliplatin (OX, a guest of CB[7]) were co-loaded onto NGO-CB[7] via π–π stacking and host–guest interactions, respectively. Subsequently, ADA-tagged hyaluronic acid (ADA-HA) wrapped NGO-CB[7] non-covalently via CB[7]-ADA host–guest interactions to improve the physiological stability and overall biocompatibility of this supramolecular nanosystem, and to enable targeted delivery into cancer cells with CD44 receptors overexpressed. Remarkably, this supramolecular nanomedicine exhibited significant antitumor efficacy via combined photothermal/photodynamic therapy (PTT/PDT) from NGO/Ce6, as well as dual chemotherapy from OX and AQ4N (activated by PDT-enhanced hypoxia), in vitro and in vivo . This study not only offers a new supramolecular inorganic/organic hybrid nanosystem for multi-modality cancer therapy, but may also provide important new insights into noncovalent functionalization of other carbon nanomaterials and inorganic nanomaterials leading to multifunctional drug delivery systems.